# How is the lasso orthogonal design case solution derived?

In orthogonal design of lasso, we get $\hat{\beta}_j^{\text{lasso}} = 0 \text{ if abs}(\hat{\beta}_j) \le \lambda /2$. WHY?

I've seen the answer and derived it myself, but don't know why.

We begin with definition of lasso, $$\hat{\beta}^{\text{lasso}} = \underset{x} {\arg\min} \sum_{i=1}^{n} ( y_i - \sum_{j=1}^{p}\beta_{ij}x_{ij} )^2 + \lambda \sum_{j=1}^{p} |\beta_j|$$

In orthogonal design case where $X^T X= I$, $\hat{\beta} = (X^TX)^{-1}X^{T}y = X^Ty$

\begin{align} L(\beta, \lambda) & = \sum_{i=1}^{n} ( y_i - \sum_{j=1}^{p}\beta_{ij}x_{ij} )^2 + \lambda \sum_{j=1}^{p} |\beta_j| \\ & = (Y - X \beta)^T(Y - X \beta) + \lambda \mathbf{I}_p \text{ abs}(\beta) \\ & = Y^TY -2\hat{\beta}^T\beta + \beta^T \beta+ \lambda \mathbf{I}_p \text{ abs}(\beta) \\ & = Y^TY + \sum_{j=1}^{p} L_j(\beta_j, \lambda) \end{align}

where $L_j(\beta_j, \lambda) = -2 \hat{\beta}_j \beta_j + 2\beta^2_j + \lambda \text{ abs}(\beta_j)$.

Leave aside $\beta_j=0$, take dereivative w.r.t. $\beta_j$ for abs$(\beta_j) > 0$, $$\frac{L_j(\beta_j, \lambda)}{\partial \beta_j} = -2 \hat{\beta}_j + 2\beta_j + \lambda \text{ sign}(\beta_j)$$

and $\hat{\beta}^{\text{lasso}}$ is either zero or solve, $$\beta_j + \lambda \text{ sign}(\beta_j) / 2 = \hat{\beta}_j,$$

which is, $$\hat{\beta}^{lasso}_j = \begin{cases} \hat{\beta}_j - \lambda/2, & \text{if } \hat{\beta}_j > \lambda/2\\ \hat{\beta}_j + \lambda/2, & \text{if } \hat{\beta}_j < -\lambda/2 \end{cases}$$

My question is the following derivation,

If abs$(\hat{\beta}_j) \le \lambda / 2$, we get $$L_j(\beta, \lambda) = -2 \hat{\beta}_j \beta_j + 2\beta^2_j + \lambda \text{ abs}(\beta_j) \ge -\lambda \text{ abs}(\beta_j) + \lambda \text{ abs}(\beta_j) \ge 0 = L_j(0, \lambda)$$ and, we can tell $\hat{\beta}_j^{\text{lasso}} = 0 \text{ if abs}(\hat{\beta}_j) \le \lambda /2$ (Why? How can you tell?)

Why $\mathbf{\hat{\beta}_j^{\text{lasso}} = 0}$? The explanation of $L_j(\beta_j, \lambda) \ge L_j(0, \lambda)$ does not seem to justify the reason.

Your derivation is not really precise, you are not really taking the derivative, but the subderivative, the function $|x|$ is not differentiable when $x = 0$. The subderivative $s$ of the absolute value when $x =0$ is $s\in [-1, 1]$

Thus, the conditions you derived are for the case where $\hat{\beta}^{lasso}_j \neq 0$ where indeed the subdifferential of the absolute value is equal the sign. But now consider the case $\hat{\beta}^{lasso}_j = 0$. By the KKT conditions, this will happen when $-\hat{\beta}_j^{ols} + s\frac{\lambda}{2} = 0$ which implies $|\hat{\beta}_j^{ols}| \leq \frac{\lambda}{2}$, since $s\in [-1, 1]$ when $\hat{\beta}^{lasso}_j = 0$.

The LASSO problem

For the sake of completeness I will write down the the lasso problem here. Our goal is to minimize

$$\min_{\beta} || Y - X\beta||_2^2 + \lambda||\beta||_1$$

where $||\cdot||_1$ is the $l_1$ norm. This a convex optimization problem, and the optimum is characterized by the KKT conditions:

$$-2X'(Y - X\beta) + \lambda s = 0$$

where $s$ is the subgradient of the $l_1$ norm, that is, $s_j = sign(\beta_j)$ if $\beta_j \neq 0$ and $s_j \in [-1, 1]$ if $\beta_j = 0$.

In the orthonormal case, $X'Y = \hat{\beta}^{OLS}$ and $X'X = I$, simplifying this to:

$$-2\hat{\beta}^{OLS} +2\beta + \lambda s = 0$$

Thus, consider the case where the solution would be $\beta_j = 0$. For this to be true we must have that $-2\hat{\beta}_j^{OLS} + \lambda s_j = 0$ which implies $|\hat{\beta}_j^{OLS}| \leq \frac{\lambda}{2}$, since $s_i \in [-1, 1]$. Since this a convex program, KKT is sufficient, and the condition works both ways, that is, $|\hat{\beta}_j^{OLS}| \leq \frac{\lambda}{2} \implies \beta_j = 0$

• I renamed loss function S to L, so the notation more consistent. But, why is $L \in [-1, 1]$? Which step of the derivation are you referring to? Jan 15, 2018 at 19:21
• The absolute value does not have a derivative when $x =0$. Recall that a derivative is the slope of the tangent line and at zero the absolute value has a "corner", you might want to check this (math.stackexchange.com/questions/991475/…). But we can extend the idea to subderivatives, and in this case it's not a single number, but a set, consisting of the slope of all lines below the function that touches the point. You might want to check this see.stanford.edu/materials/lsocoee364b/… Jan 15, 2018 at 19:25
• The part of the derivation I'm referring to is $-2 \hat{\beta}_j + 2\beta_j + \lambda \text{ sign}(\beta_j)$, where this only true for $\beta_j \neq 0$. For the case where $\beta_j = 0$, which is the case of your doubt, this should read $-2 \hat{\beta}_j + \lambda s$ where $s$ is the subdifferential of the absolute value at $0$, which is $[-1,1]$. Jan 15, 2018 at 19:46
• I was reading that this $L_j(\beta, \lambda) = -2 \hat{\beta}_j \beta_j + 2\beta^2_j + \lambda \text{ abs}(\beta_j) \ge -\lambda \text{ abs}(\beta_j) + \lambda \text{ abs}(\beta_j) \ge 0 = L_j(0, \lambda)$ implies $\hat{\beta}_j^{lasso} = 0$. Why is that? Jan 15, 2018 at 20:19
• I'm still reading your explanation with the KTT condition, which I think is different from my derivation? Jan 15, 2018 at 20:22